Leak Source Beam-forming Location of Spacecraft in Orbit Based on Dispersion Characteristics of Lamb Wave. Issue 6 (October 2020) - Qi, Lei; Feng, Yaoqi; Sun, Lichen; Li, Xi; Liao, Tao; Zhang, Yu; Rui, Xiaobo
Abstract: In recent years, the number of space debris is increasing rapidly, threatening the safety of spacecraft. More and more spacecraft are at risk of colliding with space debris, which may cause air leakages on the sealed container of spacecraft. This is a huge danger for spacecraft and astronauts. In this paper, a leak source location method based on beam-forming and dispersion characteristics of Lamb wave is proposed. The 'L' shaped sensor array with 8 acoustic emission sensors is used to collect the Lamb waves. Due to the dispersion characteristics, a 10 kHz narrow band pass filter is used firstly to process the signals. And then with a priori knowledge of guided-mode frequency dispersion curves of Lamb waves, the corresponding propagation speeds of waves are determined to obtain the time delay matrixes. By the delay-and-sum beam-forming algorithm, the leak source can be directed. The experiment result shows that the accuracy rate of the leak location is more than 90% evaluated by location error less than 5°.